Towards complexity: Training as an ethical position (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article resulted from the analysis of some of the objectives and material and immaterial phenomena involved in the Suzuki Method of Actor Training, considering its symbolic, ritual and collective dimensions. In this sense, the objective was to dialogue with the relationship between the disappearance of these instances and the wear of the idea of ​​community in contemporary world and the possibility of establishing an ethical stance towards this on the part of the performer.
Keywords: Suzuki Method of Actor Training; Intercultural dialogues; Ethical stance